Online Personas: Associations Between Focus on Self-Presentation and Social Comparison on Social Media and Mental Well-Being in Early Adolescence - Aryal, Rachana; Hjetland, Gunnhild Johnsen; Haug, Ellen; Samdal, Oddrun; Skogen, Jens Christoffer (International Journal of Public Health, 2025)
Background: The development of identity and social interactions during adolescence is increasingly intertwined with social media use. This study examines the relationship between focus on self-presentation on social media and well-being among Norwegian adolescents aged 13-15.Methods: Data from the 2022 Health Behaviour in School-Aged Children (HBSC) survey, encompassing 1,982 participants. Well-being was assessed using the WHO-5 Well-Being Index, while self-presentation focus was measured using the Self-Presentation and Upward Social Comparison Inclination Scale (SPAUSCIS). Statistical models for estimating unadjusted and adjusted associations were employed, as well as testing for age- and gender-moderation.Results: Higher focus on self-presentation was associated with lower well-being (unadjusted: β -5.1, p<0.001; fully adjusted: β -2.5, p<0.001). The association was stronger for girls (β-unadjusted -4.6, p<0.001) than boys (β-unadjusted -2.0, p<0.001). Gender-moderation was significant (p=0.012), but no age-moderation was observed (p=0.057).Conclusions: The findings indicate a negative association between focus on self-presentation and well-being, with a more pronounced effect observed in girls compared to boys. The study underscores the need for public health interventions targeting the reduction of self-presentation and social comparison behaviors on social media.